Short Communication: Structure Community of Mangrove in Peunaga Rayeuk Area, Meurebo District, Aceh West - Lisdayanti, Eka; Marlian, Neneng; Hutabarat, Malfajri; Riyanti, Levi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
This study aims to determine the structure of the mangrove community on the coast of Peunaga Rayeuk, Meurebo District, and West Aceh District. The method used in this study was line transect, making transects/plots for each observation station with a size of 10x10 m2 with 3 replications so that each observation station has an area of ​​30x10 m2. This research was conducted in October 2022. There were 2 types of mangroves included in the observation station, namely Rhizophora apiculata and Avicennia alba, while the associated mangrove was of the type Acrostichum speciosum. In addition, there are also associated mangroves that are not included in the observation station but are located around the observation station, namely Nypa fruticans, Hibiscus tiliaceus, and Pandanus odoratissima. Stations 1 and 2 were dominated by sandy and muddy sand substrates, which respectively showed a diversity index of 0.054 and 0.149, a uniformity index of 0.078 and 0.215, and a dominance of 0.478 and 0.252. The most abundant species was R.apiculata with a relative density of 0.949 ind/ha, followed by S.alba of 0.051. Relative cover of R.apiculata and S.alba respectively with the range of 0.302 and 0.698. The results of this study concluded that over all the structure of the mangrove community on the coast of Peunaga Rayeuk is still classified as low, so it requires greater attention in the restoration and management of mangrove ecosystems